Current status of the CXI beamline at the PAL-XFEL - Park, Jaehyun; Kim, Sangsoo; Nam, Ki-Hyun; Kim, Bongsoo; Ko, In Soo (Journal of the Korean Physical Society, 2016)
The Pohang Accelerator Laboratory’s X-ray free electron laser (PAL-XFEL) is a research facility currently under construction. It will provide ultra-bright (1 × 10 12 photons/pulse at 12.4 keV) and ultra-short (10 − 60 femtosecond) X-ray pulses. The CXI (coherent X-ray imaging) hard X-ray experimental station is designed to deliver brilliant hard X-rays (2 − 20.4 keV) and to measure diffraction signals with a forward scattering geometry. It will not only offer imaging studies of biological, chemical and physical samples with the “diffraction-before-destruction” scheme, but also be helpful in high-field hard X-ray physics and material science. The scientific programs are currently aimed at serial femtosecond crystallography (SFX) and coherent diffraction imaging (CDI) for bio specimens, nano materials, etc. In this paper, we describe the beamline layout, beam diagnostics, X-ray focusing optics, sample environments and detector system at the CXI experimental hutch.